Last rights? : assisted suicide and euthanasia debated - Uhlmann, Michael M; Ethics and Public Policy Center (Washington, D.C.) (1998)
"The morality of assisted suicide and euthanasia has become one of the most hotly contested issues of our time. Yet the problem is not new. The major arguments have been wrestled with both in pagan antiquity and throughout the history of the church. From Plato, Augustine, and Aquinas, from Donne and Hume to our present day, all kinds of voices have entered the fray." "This comprehensive anthology of primary sources is the essential reference work for anyone interested in understanding the arguments on both sides. The book examines the moral, theological, medical, and legal perspectives in depth, and each section of essays is accompanied by a helpful introduction guiding readers through the debate."--Jacket
Western thought on suicide: from Plato to Kant / Michael M. Uhlmann -- The history of suicide / A. Alvarez -- Do we have the right to die? / Ronald Dworkin -- The right to die-again / Hadley V. Arkes -- Ethical issues in physician-assisted suicide / Margaret Pabst Battin -- Always to care, never to kill: a declaration on euthanasia / the Ramsey Colloquium -- Jewish views on euthanasia / Byron L. Sherwin -- Rethinking life and death: a new ethical approach / Peter singer -- Death with dignity and the sanctity of life / Leon R. Kass -- The gospel of life / Pope John Paul II -- Euthanasia and Christian vision / Gilbert Meilaender -- Rethinking the Hippocratic oath / Edmund D. Pellegrino -- A fail-safe model for justifiable medically assisted suicide / Jack Kevorkian -- Why doctors must not kill / Leon R. Kass -- The case for rational suicide / Derek Humphry -- It's over, Debbie / Anonymous -- Death and dignity / Timothy E. Quill -- Active voluntary euthanasia: opening Pandora's box / D. Alan Shewmon -- Assisted suicide and euthanasia: the Dutch experience / Herbert Hendin -- Aiding the death of young children: ethical issues / H. Tristram Engelhardt, Jr. -- A statement on physician-assisted suicide ; Excerpt from Code of medical ethics / American Medical Association -- Forgoing life-sustaining treatment: the legal consensus / Alan Meisel -- Are laws against assisted suicide unconstitutional? / Yale Kamisar -- The constitution and hastening inevitable death / Robert A. Sedler -- Three court decisions: Compassion in dying v. Washington (1995) / Judge John Noonan -- Compassion in dying v. Washington (1996) / Judge Stephen Reinhardt -- Quill v. Vacco (1996) / Judge John Miner, Judge Guido Calabresi -- Assisted suicide in the United States: the 'Compassion' and 'Quill' decisions / Victor G. Rosenblum -- A model state act to authorize and regulate physician-assisted suicide / Charles H. Baron and others -- The legalization of physician-assisted suicide: creating a Potemkin village / Daniel Callahan and Margot White -- The Supreme Court decides: Washington v. Glucksberg (1997) / Chief Justice William H. Rehnquist -- Vacco v. Quill (1997) / Chief Justice William H. Rehnquist
Includes bibliographical references (pages 635-677) and indexes
Keywords: Assisted suicide; Euthanasia; Right to die; Euthanasia; Right to Die; Suicide, Assisted